Susceptibility of Candida albicans to Miconazole - Bannatyne, Robert M. (1978)
A total of 439 clinical isolates of Candida albicans were tested for susceptibility to miconazole by the agar dilution technique. When tests were read at 48 and 24 h, 56 and 84%, respectively, of the strains were completely inhibited by 4.0 μg of miconazole per ml, the estimated upper limit of probable clinical susceptibility.